ANALISIS FAKTOR-FAKTOR RENDAHNYA MINAT BELAJAR MATEMATIKA SISWA DI KELAS X SMK NEGERI 1 ANGKOLA TIMUR - Nasution, Fahmi Ferdiansyah; Ardiana, Nunik; Elindra, Rahmatika (JURNAL MathEdu (Mathematic Education Journal), 2025)
This research aims to: Analyze the factors causing students' low interest in learning in mathematics subjects at East Angkola State Vocational School. The research method used is a survey method with a qualitative approach, where in this research method data is obtained by giving a questionnaire which is then analyzed descriptively. Data analysis was carried out using the Excel computer program. The questionnaire consisted of 20 questions related to 1) feelings of happiness, 2) attention to learning, and 3) interest in the material and teacher, with 4 alternative answers on the questionnaire, namely "Always" , “Often”, “Sometimes”, and “Never”. The assessment technique is carried out using a scoring technique, namely giving points for the answers to the questionnaire that are available. The population in this study was 334 students at SMK Negeri 1 Angkola Timur for the 2022/2023 academic year. Meanwhile, the sample was 18 students of X class The results of the research show that the factors causing students' low interest in learning in mathematics are influenced (44.44%) by the teacher's sense of enjoyment of the task, so at a low level it is sufficient to determine low interest in learning mathematics. This situation is expected to increase again in the future. Keywords: Interest in Learning, Mathematics Learning